Persepsi Pelanggan Terhadap Mutu Pelayanan Kesehatan di Puskesmas Kecamatan Pasar Rebo Jakarta Timur Tahun 2015 - Yuhani Yuhani; Herlina Herlina (Jurnal Persada Husada Indonesia, 2015)
The Indonesian society at present needs quality health services which can be seen based on five quality dimensions, i.e. quick response (responsiveness), reliability, assurance, empathy and direct evidence/proof (tangibility). This case study aims to determine customers’ perception (patient and health officers) on quality health services at Pasar Rebo Sub-District of East Jakarta Community Health Centre and this study was carriedout in the month of May 2015. This type of study is a qualitative case study design. Study focus covered tangible (cleanliness, comfort, comprehensive equipments and drug availability), responsiveness (speed and service flow procedures), reliability (training, costs, officers’ responsibilities, service schedule and displinary officers), empathy (equity in services), assurance (courteous/friendly officers, safety, physically-able, intellectual officers and reward). Study samples were key and supporting informants, type of purposive sampling became the study subject for 7 informants covering: 1 Section Head Of Service as key informant and 6 supporting informants. Data collection techniques through in-depth interviews and non-participant observations. Interview guidance using a tape recorder, observation guidance using a camera and field notation. In-depth interview with quality health services key informant at Pasar Rebo Sub-District Community Health Centre was good and results of indepth interviews as well as observation on tangibility were in the passably category, while based on responsiveness, reliability, empathy, assurance dimensions were in good category. By upholding good quality health services can lead to every patients’ satisfaction seeking treatment.